Preserving heritage buildings with building information modelling: Addressing the challenges and opportunities - Mohamad Lokman, Idris; Abdul Rahimi, Abdul Rahman; Ishiyaku, Bala; Ahmad Rizal, Alias (Popular Scientist, 2024)
Preserving heritage buildings presents unique challenges in building conservation, demanding a comprehensive understanding of issues and strategic measures for long-term sustainability. The aims of this paper is to analyze the interrelationships among these organizations. The paper utilizes Cronbach's alpha reliability test, normalized mean ranking, overlap analysis, Kruskal-Wallis test, and Spearman's rank correlation for systematic data analysis. The findings of this paper will provide practical insights for organizational practitioners in identifying critical challenges and opportunities when preserving heritage building with Building Information Modelling (BIM). The paper illuminates both similarities and differences in preservation difficulties and approaches among organizations, offering profound insights into sectoral connections within the construction industry. Beyond addressing critical problems in building maintenance, this document serves as a guide for organizations navigating and overcoming hurdles in conserving heritage structures. The research outcomes offer strategic insights, promoting the development of a post-project maintenance-oriented culture. Ultimately, this contributes to enhancing the durability, efficiency, and cost-effectiveness of cultural structures in both public and private sectors.